Pengaruh Lingkungan Kerja Dan Pengalaman Kerja Terhadap Kinerja Karyawan Pada CV. Nuri Tasikmalaya - Muhamad Rafi Fauzan; Arga Sutrisna; Kusuma Agdhi Rahwana (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
The research aims to determine the effect of the work environment and work experience on the performance of CV employees. Nuri Tasikmalaya. The method used is a survey method with a quantitative approach by distributing questionnaires to 40 respondents using a saturated sampling technique, the analytical method used is multiple linear regression. Based on the results of simultaneous research work environment and work experience have a significant effect on employee performance. Partially, work environment variables have a significant effect on employee performance, and work experience variables also have a significant effect on employee performance.